Identification of the Natural Transformation Genes in Riemerella anatipestifer by Random Transposon Mutagenesis - Huang, Li; Liu, Mafeng; Ammanath, Aparna Viswanathan; Zhu, Dekang; Jia, Renyong; Chen, Shun; Zhao, Xinxin; Yang, Qiao; Wu, Ying; Zhang, Shaqiu; Huang, Juan; Ou, Xumin; et al. (Frontiers in Microbiology, 2021)
In our previous study, it was shown that Riemerella anatipestifer, a gram-negative bacterium, is naturally competent, but the genes involved in the process of natural transformation remain largely unknown. In this study, a random transposon mutant library was constructed in the R. anatipestifer ATCC11845 strain and was used to screen the genes involved in natural transformation. Among the 3000 insertion mutants, 9 mutants completely lost the ability of natural transformation, and 14 mutants showed a significant decrease in natural transformation frequency. After identification, it was shown that the genes RA0C_RS04920, RA0C_RS04915, RA0C_RS02645, RA0C_RS04895, RA0C_RS05130, RA0C_RS05105, RA0C_RS09020, and RA0C_RS04870 are essential for the occurrence of natural transformation in R. anatipestifer ATCC11845. Among them, RA0C_RS04895, RA0C_RS05130, RA0C_RS05105 and RA0C_RS04870 were putatively annotated as ComEC, DprA, ComF and RecA proteins, respectively, in the NCBI database. However, RA0C_RS02645, RA0C_RS04920, RA0C_RS04915 and RA0C_RS09020 were annotated as unknown function proteins, and they did not have any homologs among the well-characterized natural transformation machinery proteins. The homologs of these proteins are mainly distributed in the members of Flavobacteriaceae. Taken together, the results suggested that R. anatipestifer encodes unique natural transformation machinery.